Classical Educational Hadith:: Integrating Prophetic Values Into Modern Education - Miftahul Arifin; M. Suyudi; Fauzul Rhoma Dhona Oktaviyanti (El Nubuwwah Jurnal Studi Hadis, 2026)
Digital transformation in the era of Industry 4.0 disruption presents complex ethical challenges for the world of education, such as moral decline, individualism, cyberbullying and a lack of spirituality amongst learners. Although much research has been conducted on hadis in education, there remains a research gap in the form of a methodological disparity between textual-normative studies of classical literature and the practical, applied needs of the modern era. This study aims to fill this gap by analysing the systematic integration of educational principles found in classical hadis into the dynamics of modern education today. The research method employed is descriptive qualitative, utilising a literature review (library research). The approach adopted is philosophical-epistemological, through a thematic interpretation of authoritative texts such as Sahih al-Bukhari, Sahih Muslim, Ihya’ Ulum al-Din, and Ta’lim al-Muta’allim. The research findings indicate that classical hadis remain relevant as educational guidelines through the reinforcement of the value of purification of the soul (tazkiyah al-nafs), the prioritisation of adab over knowledge, and the revitalisation of the teacher’s role as a moral pillar. The key findings emphasise that prophetic values such as tabayyun and uswah hasanah are crucial counterpoints in addressing the crisis of ethical communication in the digital sphere. The novelty of this research lies in its attempt to bridge the gap between classical intellectual traditions and the pedagogical needs of the 21st century through a religious-humanist educational framework. This research concludes that the integration of classical values can create a more holistic educational system for shaping well-rounded individuals who are adaptable yet maintain their integrity amidst the tide of modernity.